IgG4-related disease: a rare but treatable cause of refractory intracranial hypertension. Issue 3 (11th December 2015) - Williams, Thomas; Marta, Monica; Giovannoni, Gavin
Abstract : Hypertrophic pachymeningitis secondary to IgG4-related disease is a rare but sometimes devastating cause of intracranial hypertension. It has the potential for an excellent response to corticosteroids or rituximab. We discuss the clinical presentation, imaging, histology (with its difficult distinction from lymphoma), management and follow-up of a case, including relapse and re-treatment following an initial response to rituximab.